Dampak Pandemi Covid-19 terhadap Bisnis Warung dan Restoran di Wilayah Kendari Beach Kecamatan Kendari Barat Kota Kendari - Hisma Mutiyah; Saediman Saediman; Hidrawati Hidrawati (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2024)
Kendari Beach is said to be strategic because it is crowded with residents both in the city and outside the city of Kendari to just hang out, go for a walk or enjoy various culinary delights. The Covid-19 pandemic has had an impact on the shop and restaurant business. The purpose of this study was to determine the impact of the Covid-19 pandemic on shop and restaurant businesses in terms of work environment, workforce, procurement of raw materials, number of customers and business turnover and income in the Kendari Beach area, West Kendari District, Kendari City. The determination of the research area was carried out purposively with the consideration that the Kendari Beach area is one of the culinary tourism areas that is quite popular with the community. The number of respondents in this study were 28 shop businesses and 3 restaurant businesses. Data analysis used descriptive analysis through a Likert scale and quantitative analysis through paired t tests. The results of the study show that the Covid-19 pandemic has no impact on employment and raw material procurement. However, the Covid-19 pandemic has had quite an impact on the environment and work operations. Furthermore, the Covid-19 pandemic has greatly impacted the number of customers as well as turnover and income. The strategy adopted by several shop and restaurant businesses in the Kendari Beach area to maintain and develop their business is to open a business earlier than usual and comply with all the requirements in order to receive assistance from the government.